ECONOMIC POLICIES IN IRAQ AND WAYS OF ECONOMIC REFORM (American Journal of Business Management, Economics and Banking, 2023)
Economic reform is a goal that most countries seek to achieve, especially countries with fragile economies, by following ideologies and economic policies aimed at bringing the economic reality towards a stable economy capable of confronting economic crises and imbalances At the global and local level, and because the Iraqi economy suffers from its weak ability to confront the global shocks of oil prices due to its almost complete reliance on oil rent revenues and the underdevelopment of its productive sectors in all its branches, which was reflected in the imbalance in its internal balances And external and widening gaps in its economic variables, so it is necessary to intensify efforts and follow corrective economic mechanisms and policies on the overall macro levels of the Iraqi economy Balanced and advancing economic growth by following stabilization and economic adjustment policies to balance supply and demand on the public and private economic levels